Social Cognitive Role of Schizophrenia Candidate Gene GABRB2 - Tsang, Shui Ying (Public Library of Science, 2013)

(untitled)
The occurrence of positive selection in schizophrenia-associated GABRB2 suggests a broader impact of the gene product on population fitness. The present study considered the possibility of cognition-related GABRB2 involvement by examining the association of GABRB2 with psychosis and altruism, respectively representing psychiatric and psychological facets of social cognition. Four single nucleotide polymorphisms (SNPs) were genotyped for quantitative trait analyses and population-based association studies. Psychosis was measured by either the Positive and Negative Syndrome Scale (PANSS) or antipsychotics dosage, and altruism was based on a self-report altruism scale. The minor alleles of SNPs rs6556547, rs1816071 and rs187269 in GABRB2 were correlated with high PANSS score for positive symptoms in a Han Chinese schizophrenic cohort, whereas those of rs1816071 and rs1816072 were associated with high antipsychotics dosage in a US Caucasian schizophrenic cohort. Moreover, strongly significant GABRB2-disease associations were found among schizophrenics with severe psychosis based on high PANSS positive score, but no significant association was observed for schizophrenics with only mild psychosis. Interestingly, in addition to association with psychosis in schizophrenics, rs187269 was also associated with altruism in healthy Han Chinese. Furthermore, parallel to correlation with severe psychosis, its minor allele was correlated with high altruism scores. These findings revealed that GABRB2 is associated with psychosis, the core symptom and an endophenotype of schizophrenia. Importantly, the association was found across the breadth of the psychiatric (psychosis) to psychological (altruism) spectrum of social cognition suggesting GABRB2 involvement in human cognition.